Pencarian Materi Kuliah Pada Aplikasi Blended Learning Menggunakan Metode Vector Space Model - Putra Angga; Lastri Widya Astuti; Mustafa Ramadhan (Ultimatics : Jurnal Teknik Informatika, 2016)
Searching for a lot of materials are materials which is needed quickly and accurately. are by ranking them. Ranking is one branch of science of information retrieval. Information document search Vector Space Model (VSM). VSM uses the concept which is included in linear algebra is a vector space. Based on the concept that is used, the development of blended learning application uses space vector modeling method as an alternative for students in searching of relavan material toward materials needed, reducing the error level in the return of information and students can achieve goals quickly. Column vector representation is used in the conversion of document input, processing and output. Another concept that is used to determine the proximity between two vectors, are by calculating the angle formed between the two vectors and then it is sequenced from the data which has a large angle of the smallest to the largest of which indicates the sequence data of the ranking from the most relevant to irrelevant. In this study is described about the will produce quality to each document to determine how relevant the document to the query. Quality method which is used in the implementation can be a combination of TF (Term Frequency), IDF (Inverse Document Frequency), and the corresponding normalized input from the user. Index Terms— Content Search, Blended learning, the Vector Space Model.